Big-Time Small-Scale Innovations - Van Es, Corline (Institutional Knowledge at Singapore Management University, 2009)
Is there value in supporting small-scale, yet innovative projects? Based on their experience in Digital Pioneers – a programme supporting innovative Dutch civil society initiatives – Corline Van Es and Chris Sigaloff of Kennisland, Netherlands, make a case for this latest sector trend and the support it deserves.